Dithiothreitol-based protein equalization technology to unravel biomarkers for bladder cancer - Araújo, José E. (2018)
The PROTEOMASS Scientific Society is acknowledged by the funding provided to the Biological Mass Spectrometry Isabel Moura. Authors acknowledge the funding provided by UCIBIO, Unidade de Ciencias Biomoleculares Aplicadas, which is financed by national funds from FCT/MEC (UID/Multi/04378/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728) and to the Associate Laboratory for Green Chemistry LAQV which is financed by national funds from FCT/MEC (UID/QUI/50006/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265). J. E. Araujo acknowledges the financial support given by the Portuguese Foundation for Science and Technology under doctoral grant number SFRH/BD/109201/2015. H. Lopez-Fernandez is supported by a post-doctoral fellowship from Xunta de Galicia. H.M.S. is funded by the FCT Investigator Programme 2015 (IF/00007/2015). The Nova Medical School is also acknowledged for financial support under project "Discovery of biomarkers for bladder carcinoma diagnosis" - NOVA health programme 2015.